LTE 기반 FOTA 기술을 통한 IoT 펌웨어 업데이트 설계 및 구현 - 서진호 (The Graduate School, Ajou University, 2024)
IoT (Internet of Things) 기술의 발전과 함께, 다양한 장비들이 네트워크에 연 결되어 있으며, 이러한 장비들의 안정적이고 효율적인 운영을 위해서는 주기적인 Firmware 업데이트가 필수적이다. 네트워크 통신 모듈이나 GPS, CAN통신, 각 종 센서 등이 탑재되어 있는 고정된 IoT(스마트홈, 스마트팜 등) 장비 뿐만 아니 라 이동하는 IoT장비(자동차, BIKE)의 Firmware의 업데이트를 유선 통신이나 범위가 한정적인 WI-FI 통신 또는 Bluetooth 통신이 아닌, 어디서나 업데이트를 진행하기 위해서는 광대역의 무선 통신으로 적용해야만 주기적이고 즉각적인 수 정과 개선이 가능하다. 이처럼 원격으로 Firmware를 업데이트를 하는 기술을 FOTA(Firmware Over-The-Air )라고 한다. WI-FI나 Bluetooth로도 FOTA 기술을 사용할 수 있 지만 앞서 말했듯이 어디서든 스마트폰, 테블릿은 물론 IoT 장비, 자동차, BIKE 등과 같은 다양한 전자 장비들에 Firmware를 무선 네트워크를 통하여 업데이트 를 할 수 있으려면 광대역의 통신망을 이용하여야 한다. 본 논문에서는 시장 조사 및 타제품 리서치 후 선정된 개발모듈 중에 LTE-CatM1 통신 모듈인 BG96과 IoT 장비의 개발에 특화되어 있는 MCU인 ESP32–S3를 사용하여 BIKE의 위치와 속도 배터리 잔량에 대한 데이터를 서버 로 보내는 IoT 단말기를 개발하여 LTE 통신을 이용한 FOTA에 대해 연구를 진 행 하였다. 해당 연구에서의 초점은 저비용과 업데이트의 정확도와 성공률을 향 상시키는 데 목표 및 중요성을 두고 연구개발을 진행하였다. FOTA는 현대 전자 장비의 필수적인 기능이 되어가고 있으며, 이는 특히 IoT 환경에서 더욱 중요해지고 있다. FOTA의 핵심 장점은 사용자가 제품의 업데이 트를 물리적인 케이블 연결이나, 서비스 센터 등을 가는 복잡한 절차를 거치지 않고도 자동적으로 제품의 새로운 기능이 추가되거나 보안 취약점이 발견되었을 때, 제조사는 빠르게 Firmware의 업데이트를 진행하여 문제를 해결할 수 있기에 사용자의 시간 및 비용을 절감할 수 있다.|With the advancement of IoT (Internet of Things) technology, a wide range of devices are now connected to networks, and regular firmware updates are crucial for their stable and efficient operation. This applies not only to stationary IoT devices, such as those in smart homes and smart farms, equipped with network communication modules, GPS, CAN communication, and various sensors, but also to mobile IoT devices like cars and bikes. To facilitate updates from anywhere, these devices need to utilize wideband wireless communication instead of limited wired, Wi-Fi, or Bluetooth connections, allowing for periodic and immediate modifications and improvements. This technology of remotely updating firmware is known as FOTA (Firmware Over-The-Air). While FOTA can be implemented using Wi-Fi or Bluetooth, as mentioned earlier, to enable updates in various electronic devices such as smartphones, tablets, IoT devices, cars, and bikes from anywhere, it is necessary to use a wideband communication network for wireless firmware updates. In this research paper, after conducting market research and analyzing competitive products, we selected development modules including the LTE-CatM1 communication module BG96 and the IoT-specialized MCU ESP32–S3. Using these, we developed an IoT terminal for bikes that transmits data such as location, speed, and battery level to a server. We conducted research on FOTA using LTE communication, focusing on low-cost solutions and improving the accuracy and success rate of updates. The emphasis of this research was on achieving cost-effectiveness and enhancing the precision and reliability of the updates. FOTA is becoming an essential function in modern electronic equipment, especially in the IoT environment. The key advantage of FOTA is that it allows users to update their products automatically without going through complex procedures such as physical cable connections or visits to service centers. When new features need to be added or security vulnerabilities are discovered, manufacturers can quickly roll out firmware updates to address these issues, thereby saving users' time and costs.
학위논문(석사)--지능형소프트웨어,2024. 2
Keywords: FOTA; LTE